2015
DOI: 10.1016/j.jtcvs.2014.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility and intermediate outcomes of using a handcrafted, area-preserving, bifurcated Y-graft modification of the Fontan procedure

Abstract: The area-preserving, bifurcated Y-graft Fontan modification is technically feasible and shows excellent intermediate outcomes. Additional study is required to determine whether the advantages seen in the computational models will be realized in patients over the long-term, and to optimize patient selection for each of the various Fontan options now available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Moreover, simulation-derived designs from SimVascular have been translated to clinical use, an example of which is the pilot study of the Fontan Y-graft. 34,37 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, simulation-derived designs from SimVascular have been translated to clinical use, an example of which is the pilot study of the Fontan Y-graft. 34,37 …”
Section: Resultsmentioning
confidence: 99%
“…With regard to new technical options, Marsden et al tested a Y-shaped extra-cardiac Fontan baffle using a CFD model [25], and demonstrated the technical feasibility and intermediate outcomes of this modification in six patients [26]. Their results indicate that the procedure may be an option for high-risk patients (with discordant anatomy) during bilateral BCPS.…”
Section: Therapeutic Options and New Techniquesmentioning
confidence: 99%
“…Continual efforts are made to improve the surgical techniques used in Fontan surgery. Recently, a Y-shaped graft was proposed for the connection of the inferior vena cava to the left and right pulmonary artery 139 . Theoretically, this graft is more energetically favorable and provides better distribution of hepatic blood flow between the left and right pulmonary artery, distributing “hepatic factors” that may prevent the formation of intrapulmonary collaterals more equally.…”
Section: State Of the Artmentioning
confidence: 99%